FROM MAXIMUM COLLEGE TO THE NATIONAL LIBRARY: USES AND REDEFINITION OF A LIBRARY IN CHILE (1767-1813) - Gutiérrez Ramírez, Eduardo (Revista de Historia Social y de las Mentalidades, 2024)
The following article seeks to track the library  that belonged to the Society of Jesus in colonial  Santiago, which was extensively used during the  presence of the Order in Chile, and after their  expulsion would be subject to various policies and  actions  by the Crown, and then by the first Chilean  republican governments. Thus, the library would  settle the basis of Chilean culture.
Keywords: Jesuit; Jesuit College; Maximum College,; National Library; Written culture; Redefinition